2017
DOI: 10.1158/2326-6066.cir-16-0125
|View full text |Cite
|
Sign up to set email alerts
|

Macropinocytosis of Nab-paclitaxel Drives Macrophage Activation in Pancreatic Cancer

Abstract: Pancreatic cancer is a devastating disease that is largely refractory to currently available treatment strategies. Therapeutic resistance is partially attributed to the dense stromal reaction of pancreatic ductal adenocarcinoma (PDAC) tumors that includes a pervasive infiltration of immunosuppressive (M2) macrophages. Nab-paclitaxel (trade name Abraxane) is a nanoparticle albumin-bound formulation of paclitaxel that, in combination with gemcitabine, is currently the first line treatment for pancreatic cancer. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
104
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(113 citation statements)
references
References 46 publications
2
104
0
1
Order By: Relevance
“…The anti-tumor activity of macrophages ensues partly from NOS2 expression. NOS2 encodes inducible nitric oxide synthase (iNOS), an enzyme that catalyzes the production of tumoricidal reactive oxygen species (8). While the expression level of IL-6, IL-1b, and NOS2 for the Resiquimod and LPS treatment groups were considerably enhanced, TNF-α expression was relatively modest.…”
Section: Characterization Of In Vitro Activation Of Bmdm By Resiquimodmentioning
confidence: 99%
See 1 more Smart Citation
“…The anti-tumor activity of macrophages ensues partly from NOS2 expression. NOS2 encodes inducible nitric oxide synthase (iNOS), an enzyme that catalyzes the production of tumoricidal reactive oxygen species (8). While the expression level of IL-6, IL-1b, and NOS2 for the Resiquimod and LPS treatment groups were considerably enhanced, TNF-α expression was relatively modest.…”
Section: Characterization Of In Vitro Activation Of Bmdm By Resiquimodmentioning
confidence: 99%
“…Signaling interactions between cancer cells and neighboring immune cells lead to the protumorigenic evolution of the latter, yielding cells that lack anti-tumor properties (7). For instance, a major proportion of the tumorassociated macrophages (TAMs) display an alternatively activated endotype, causing a shift in the Th1/Th2 cytokine balance towards a more Th2-like (anti-inflammatory) activity, rendering an immunosuppressive niche conducive to tumor growth (8). Additionally, TAMs can dampen the adaptive immune response by impeding the tumor infiltration of CD8+ cytotoxic T cells (9).…”
Section: Introductionmentioning
confidence: 99%
“…Table 7B lists the nanodelivery systems that may achieve anticancer effects via macrophages. [95][96][97] Interestingly, it was found that a part of Abraxane's activity may be derived from its activity in increasing the CD80 + CD86 + M1 macrophage subpopulation that works in an antagonistic manner to the M2 subpopulation. 95 Regardless, macrophage-based nanotherapy remains in exploratory stage and more studies are needed to substantiate its potential.…”
Section: Nanotherapy Of Tammentioning
confidence: 99%
“…114,115 Additionally, there is work citing that the efficacy of nab-paclitaxel is actually dependent upon drug internalization by TAMs via macropinocytosis. 116 There are currently clinical trials in PDAC forthcoming utilizing vitamin D analogs as a stromal remodeling mechanism (NCT02930902, NCT02030860).…”
Section: Secreted Protein Acid and Rich In Cysteine (Sparc)mentioning
confidence: 99%
“…However, the levels of SPARC expression did not appear to correlate with response to treatment . Additionally, there is work citing that the efficacy of nab ‐paclitaxel is actually dependent upon drug internalization by TAMs via macropinocytosis . Therefore, targeting the optimization of macropinocytosis may be an additional option to improving nab ‐paclitaxel efficacy.…”
Section: Introduction: Pancreas Cancermentioning
confidence: 99%